A multi-isotope approach reveals seasonal variation in the reliance on marine resources, production of metabolic water, and ingestion of seawater by two species of coastal passerine to maintain water balance - Navarrete, Lucas; Lübcker, Nico; Alvarez, Felipe; Nespolo, Roberto; Sanchez-Hernandez, Juan Carlos; Maldonado, Karin; Sharp, Zachary D.; Whiteman, John P.; Newsome, Seth D.; Sabat, Pablo (Frontiers in Ecology and Evolution, 2023)
Tracing how free-ranging organisms interact with their environment to maintain water balance is a difficult topic to study for logistical and methodological reasons. We use a novel combination of triple-oxygen stable isotope analyses of water extracted from plasma (δ16O, δ17O, δ18O) and bulk tissue carbon (δ13C) and nitrogen (δ15N) isotopes of feathers and blood to estimate the proportional contribution of marine resources, seawater, and metabolic water used by two species of unique songbirds (genus Cinclodes) to maintain their water balance in a seasonal coastal environment. We also assessed the physiological adjustments that these birds use to maintain their water balance. In agreement with previous work on these species, δ13C and δ15N data show that the coastal resident and invertivore C. nigrofumosus consumes a diet rich in marine resources, while the diet of migratory C. oustaleti shifts seasonally between marine (winter) to freshwater aquatic resources (summer). Triple-oxygen isotope analysis (Δ17O) of blood plasma, metabolic rate (BMR), and total evaporative water loss (TEWL) revealed that ~25% of the body water pool of both species originated from metabolic water, while the rest originated from a mix of seawater and fresh water. Δ17O measurements suggest that the contribution of metabolic water tends to increase in summer in C. nigrofumosus, which is coupled with a significant increase in BMR and TEWL. The two species had similar BMR and TEWL during the austral winter when they occur sympatrically in coastal environments. We also found a positive and significant association between the use of marine resources as measured by δ13C and δ15N values and the estimated δ18O values of ingested (pre-formed) water in both species, which indicates that Cinclodes do not directly drink seawater but rather passively ingest when consuming marine invertebrates. Finally, results obtained from physiological parameters and the isotope-based estimates of marine (food and water) resource use are consistent, supporting the use of the triple-oxygen isotopes to quantify the contribution of water sources to the total water balance of free-ranging birds.